Princess Mia - Cabot, Meg (New York, NY HarperTeen, 2008)
While Mia tries to get over breaking up with her boyfriend, she discovers a diary kept by a former princess of Genovia from the 1600s, the contents of which could change the fate of her country forever
1
NEW, LITERATURE
Keywords: Diaries -- Fiction; High schools -- Fiction; Princesses -- Fiction; Schools -- Fiction; Self-confidence -- Fiction; New York (N.Y.) -- Fiction